Exploiting DNA markers for the botanical origin identification of honey - Soares, Sónia (2014)
Honey is a natural product highly consumed due its known associalion wilh heallh benefits. Monofloral and Protecled Designation 01 Origin (PDO) honeys have generally higher economic value since Ihey are considered to have higher quality due lo its specific and well-delined flavor and aroma, Thus, these products are susceptible to misleading labeling and Iraudulenl praclices, making their assessment 01 bolanical origin and authentication a task of utmost importance. For this purpose, traditional methods based on pollen idenlification by microscopic analysis are presently used. However, Ihis is lime consuming and greatly depends on lhe experience and skill of Irained analysls [1] Recently, due to its high specificity and sensitivity, DNA-based methods are emerging as allernative tools lor food authenlication since they allow the unequivocal species identification